Who guards the guardians and how democratic civil-military relations - edited by Thomas C. Bruneau and Scott D. Tollefson (Austin University of Texas Press, 2006)
The continued spread of democracy into the twenty-first century has seen two-thirds of the almost two hundred independent countries of the world adopting this model. In these newer democracies, one of the biggest challenges has been to establish the proper balance between the civilian and military sectors. A fundamental question of power must be addressed?who guards the guardians and how?
Includes index
Keywords: Civil supremacy over the military